Evaluation Of The Effect Of Vertical Load On The Impedance Function In Seismic Analysis Of Soil-Pile-Structure Interaction - Ahmad Mahboubi (Deep Foundations Institute, 2010)
The damage caused by catastrophic earthquakes has always been an incentive towards more sophisticated building codes and requirements. In parallel to computer technology development, the engineers? attitude towards acquisition of more accurate results is increasing. This approach leads to designation of structural elements with more elaboration considering different aspects of their behavior. In addition, less simplified methods will be considered as satisfactory for analyzing such problems. The problem of soil-pile-structure interaction is one of the phenomena that can be included in this category. In general, there are two methods by which the study of soil-pile interaction phenomenon is studied. These include direct and sub-structuring methods. The sub-structuring approach relies on the linear or slightly non-linear behavior of soil since it employs the results of kinematic interaction analyses for inertial interaction studies. In the past, the kinematic interaction between pile-soil was considered as negligible. This was due to the softer nature of the surrounding soil that increased the time period of vibrations. However, more research revealed that although this approach was consistent in many cases, there were some sites where the time period decreased. This was due to the material properties of the foundation and the soil, in a way that caused the frequency of vibration meet natural frequency of the system. The second type of interaction is the inertial interaction which reflects the effect a structure on top exerts on the oscillation experienced by the foundation. This paper examines the impact of vertical load on the inertial interaction by virtue of impedance functions. Three different load cases for the structure at the top of a pile foundation were considered for the analyses conducted in this study. The changes in the stiffness and damping of the system by frequency are studied and finally, the results are presented.